2019
DOI: 10.1088/1361-6528/ab139c
|View full text |Cite
|
Sign up to set email alerts
|

Questioning liquid droplet stability on nanowire tips: from theory to experiment

Abstract: Liquid droplets sitting on nanowire (NW) tips constitute the starting point of the vapor-liquidsolid method of NW growth. Shape and volume of the droplet have been linked to a variety of growth phenomena ranging from the modification of growth direction, NW orientation, crystal phase, and even polarity. In this work we focus on numerical and theoretical analysis of the stability of liquid droplets on NW tips, explaining the peculiarity of this condition with respect to the wetting of planar surfaces. We highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…11) as the wire cross-section area is rapidly reduced, while the catalyst droplet 'lifts off' the substrate surface. [58,219], Surface adsorbates, which alter nanowire sidewall energies, can promote kinking, as observed for the case of Au sidewall wetting during VLS growth of Si nanowires [179]. Filler et al have shown that intentional kinking of Si nanowires [215] and subeutectic VLS growth of Ge nanowires [220], in both cases using Au catalysts, are strongly influenced by hydrogen adsorption on the wire sidewalls.…”
Section: Orientation Control and Substrate Effects For Grown Nanowiresmentioning
confidence: 97%
See 1 more Smart Citation
“…11) as the wire cross-section area is rapidly reduced, while the catalyst droplet 'lifts off' the substrate surface. [58,219], Surface adsorbates, which alter nanowire sidewall energies, can promote kinking, as observed for the case of Au sidewall wetting during VLS growth of Si nanowires [179]. Filler et al have shown that intentional kinking of Si nanowires [215] and subeutectic VLS growth of Ge nanowires [220], in both cases using Au catalysts, are strongly influenced by hydrogen adsorption on the wire sidewalls.…”
Section: Orientation Control and Substrate Effects For Grown Nanowiresmentioning
confidence: 97%
“…This derivation of what is known as the Nebol'sin-Shchetinin criterion has been very often used to explain and calculate the equilibrium contact angle of catalyst droplets on top of the nanowires. Recently, the limitations of using this expression have been elucidated [58]. In the Nebol'sin-Shchetinin criterion, G o is minimized by varying R, which at the same time has an impact on the liquid-solid interface energy, and it is obviously not a free parameter.…”
Section: Contact Anglementioning
confidence: 99%
“…Due to the pinning of the liquid at the edge of the faceted nanowires, an increase in the liquid volume results in the increase of the apparent contact angle. 56 The normalised surface energy increases with the liquid volume due to the expansion and deformation of the liquid surface at the edges. The lowest normalised surface energy corresponds to the configuration with hexagonal nanowire cross-section, where the droplet is the least deformed.…”
Section: Zigzag Mechanismmentioning
confidence: 99%
“…Thus, the droplet manipulation is very difficult. Fontcuberta et al developed a creative droplet manipulation method [48]. By annealing under the vacuum, they increased the droplet size by tip thermal decomposition and successfully removed the droplet from the NW top to the sidewalls.…”
Section: Introductionmentioning
confidence: 99%